Second-generation cryoballoon for pulmonary vein isolation in patients with pulmonary vein abnormality: Safety, efficacy and lessons from re-ablation procedures. (1st December 2018) - Yalin, Kivanc; Lyan, Evgeny; Abdin, Amr; Heeger, Christian-Hendrik; Vogler, Julia; Liosis, Spyridon; Eitel, Ingo; Meyer-Saraei, Roza; Elsner, Christian; Eitel, Charlotte; Tilz, Roland Richard
Abstract: Second generation cryoballoon (CB) has been shown to be effective for treatment of paroxysmal and persistent atrial fibrillation (AF). However, the fixed size of the non-compliant balloon may limit its use in patients with pulmonary vein (PV) abnormalities. In this study we investigated the acute success, procedural complications and long term outcome of CB based PV isolation (PVI) in patients with PV abnormality. A total of 238 patients [64.8 ± 11.1 years; 91 paroxysmal (38.2%), 147 persistent AF (61.8%)] underwent PVI using the second generation CB without preprocedural imaging. In 43/238 (18.1%) patients PV abnormality (left common PV in 26, right middle PV in 20) was observed. All targeted veins including abnormal PVs were isolated (100%). Transient phrenic nerve palsy (PNP) occurred in one (2.3%) patient in the PV anomalous group and 6 (3.0%) in the control group (p = NS). There was no other adverse event including PV stenosis, atrio-esophageal fistula or cerebrovascular events related to the procedure. During mean follow-up of 11.8 ± 5.4 month a total of 59 patients (24.7%) had atrial tachyarrhythmia (ATA) recurrence [27 (11.3%) had AT recurrence]. In the PV anomalous group, 20/43 (46.5%) patients had ATA recurrence compared to 39/195 (20%) in the control group (p < 0.001). AT recurrence was observed in 27 (11.3) patients [11 (25.5%) in the PV anomalous group and 16 (8.2%) in controls respectively, p = 0.003]. In patients with PV abnormality CB-based AF ablation results in a similar acute PVI rate but a higher ATA recurrence rate during follow up as compared to patients without PV abnormality. Highlights: The prevalence of LCPV with a length of >10 mm is 10.9% and of the RMPV 7.1%. Use of CB-2 for patients with LCPV and RMPV is safe and has similar acute results but a higher recurrence rate as compared to patients without PV abnormality. Ablation along the right PVs in patients with RMPV may result in substrate formation for non-CTI-dependent right atrial tachycardia.